A drug evaluation of 1% tenofovir gel and tenofovir disoproxil fumarate tablets for the prevention of HIV infection - Gengiah, Tanuja N (2012)
INTRODUCTION: More than a million people acquire HIV infection annually. Pre-exposure prophylaxis (PrEP) using antiretrovirals is currently being investigated for HIV prevention. Oral and topical formulations of tenofovir have undergone pre-clinical and clinical testing to assess acceptability, safety and effectiveness in preventing HIV infection. AREAS COVERED: The tenofovir drug development pathway from compound discovery; pre-clinical animal model testing and human testing were reviewed for safety, tolerability, and efficacy. Tenofovir is well tolerated and safe when used both systemically or applied topically for HIV prevention. High drug concentrations at the site of HIV transmission and concomitant low systemic drug concentrations are achieved with vaginal application. Coitally applied gel may be the favoured prevention option for women compared to the tablets which may be more suitable for prevention in men and sero-discordant couples. However, recent contradictory effectiveness outcomes in women need to be better understood. EXPERT OPINION: Emerging evidence has brought new hope that antiretrovirals can potentially change the course of the HIV epidemic when used as early treatment for prevention, as topical or oral PrEP. Although some trial results appear conflicting, behavioral factors, adherence to dosing, and pharmacokinetic properties of the different tenofovir formulations and dosing approaches offer plausible explanations for most of the variations in effectiveness observed in different trials.